Giant trochanteric pressure sore: Use of a pedicled chimeric perforator flap for cover - Sandeep Mehrotra (Indian Journal of Plastic Surgery)
Pressure sores are increasing in frequency commensurate with an ageing population with multi-system disorders and trauma. Numerous classic options are described for providing stable wound cover. With the burgeoning knowledge on perforator anatomy, recent approaches focus on the use of perforator-based flaps in bedsore surgery. A giant neglected trochanteric pressure sore in a paraplegic is presented. Since conventional options of reconstruction appeared remote, the massive ulcer was successfully managed by a chimeric perforator-based flap. The combined muscle and fasciocutaneous flaps were raised as separate paddles based on the anterolateral thigh perforator branches and provided stable cover without complications. Perforators allow versatility in managing complex wounds without compromising on established principles.